2020
DOI: 10.3390/su12145691
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Evaluation of Clinch Connections of Thin-Walled Building Structures

Abstract: The high energy intensity of industry and the importance of natural resources are currently much-discussed topics. Light steel structures made from thin-walled cold-formed (TWCF) profiles play an important role in this discussion because their increased use has significantly reduced the consumption of conventional structural steel. New, more efficient technologies for connections of the TWCF structures, such as punch riveting and clinching, are being developed, which are advantageous in terms of cost and time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Experiments have often been used to adjust tool geometry and process parameters in the clinching process, which take a lot of time and quite expensive. To overcome this problem, the nite element method is frequently used to investigate the joining process, mechanical properties, and failure mechanisms of the clinched joints [25]. Wang et al[26] carried out the investigations and modeling for clinch joining process design using nite element simulation.…”
Section: Modelmentioning
confidence: 99%
“…Experiments have often been used to adjust tool geometry and process parameters in the clinching process, which take a lot of time and quite expensive. To overcome this problem, the nite element method is frequently used to investigate the joining process, mechanical properties, and failure mechanisms of the clinched joints [25]. Wang et al[26] carried out the investigations and modeling for clinch joining process design using nite element simulation.…”
Section: Modelmentioning
confidence: 99%
“…Flodr et al [96], Berezhnoi et al [97], and Jonas et al [98] studied the mechanical properties of the clinched joint using the finite elements method. The authors found the functional relationship between forming force and geometry of clinched joint.…”
Section: Steel Sheetmentioning
confidence: 99%
“…The subject of a thin-walled structure is frequently analyzed in the literature [44]. The research mainly includes inter alia, strength analysis [45], stability assessment [46] and the very important aspect of structure joining [47,48]. The considered detail is a product manufactured by the facility from small and medium-sized enterprises.…”
Section: Problem Of Robotic Welding Under Constraintmentioning
confidence: 99%